Knowledge, attitude, and practice of fire safety systems and preparedness among students at higher learning institutions / Nur Aliesa Mohd Zul ... [et al.] - Mohd Zul, Nur Aliesa; Wan Sulaiman, Wan Zaiton; Mohd Mokhtar, Khairiah; Suhaimi, Nurud Suria; Fauzan, Nur Syafiqah; Rani, Siti Ilyani (Penerbit UiTM (UiTM Press), 2024)
The main objective of this study is to determine the level of knowledge, attitude, and practice (KAP) regarding fire safety systems and preparedness among students at Universiti Islam Pahang Sultan Ahmad Shah (UniPSAS). A cross-sectional survey was conducted to explore the knowledge, attitudes, and practices (KAP) regarding fire safety among students at Universiti Islam Pahang Sultan Ahmad Shah (UniPSAS). The survey collected data from a diverse group of students across different departments at a single point in time. Researchers used a structured questionnaire to evaluate how well students understood fire safety, their attitudes, and how they practiced safety measures. The survey included various campus facilities. A cross-sectional survey, which consists of two main sections, was conducted. The first section focuses on sociodemographic information, and the second delves into the KAP components. The questionnaire aims to gauge students' understanding, thoughts, and actions related to fire safety and preparedness during a fire incident. A total of 157 students participated in the study. Over half of the participants have good knowledge, positive attitudes, and good practices toward fire safety systems and preparedness. However, very few participants know how to use fire control measures in case of a fire accident. The study findings indicate that UniPSAS students exhibit a commendable level of awareness regarding fire safety, coupled with a moderate understanding of fire safety measures.